WOMAN STRUGGLE IN PAULO COELHO’S THE SPY - EKA NOVIYANTI; AMRIN SARAGIH; MUHAMMAD NATSIR (State University of Medan, 2020)
This study discussed woman struggle in Paulo Coelho’s The Spy. The objectives were to find out the kinds of woman’s struggle in Novel The Spy, the ways the main character struggles to fulfill her needs, and the reasons why the main character struggle in the way she did. This study used descriptive qualitative method. This study used Maslow (1987) theory to analyze the kinds of woman’s struggle and the ways the main character struggles to fulfill her needs that she had faced and elaborated the reasons by using theory of ambition. The result of this study can be concluded in some aspects. First, the kinds of woman’s struggle found in Novel The Spy in fulfilling the human needs, namely: Struggle for Survival, Struggle to Reach the Dream, Struggle for Love & Relationship, Struggle in Getting A Good Reputation and Struggle to be Independent Woman. Second, the ways the main character struggles to fulfilling her needs are exchange sex with favors and money, making relations with men from the higher classes and to be a Spy. Third, the reasons why the main character struggle are because of her ambition to become a Free Woman and influenced by author’s background.